Investigations on printing path dependent properties of additively manufactured samples using micro computed tomography. Issue 9 (7th August 2020) - Englert, Lukas; Dietrich, Stefan; Pinter, Pascal
Abstract : Purpose: The purpose of this paper is to understand the relationship between defect properties and the tool path used for generating additively manufactured parts. The correlation between processing strategy and porosity architecture is one of the key aspects for a precise understanding of defect formation and possibilities for defect reduction. Design/methodology/approach: The authors present a new combined geometry, processing path and porosity analysis procedure based on the use of x-ray computed micro tomography image data and numerical control programming code. The procedure allows for a covisualisation of the track of the respective processing head with the three-dimensional microstructure data. Findings: The presented method yields statistical results about defect distribution and morphologies introduced by the respective process characteristics in parts. The functionality of the proposed procedure is demonstrated on an aluminum (AlSi10Mg) and a polylactide test sample to show the additional insight found for both additive manufacturing processes and the resulting microstructural properties. Originality/value: The novelty of this paper is the analysis of the porosity with respect to the underlying additive process zone and the sample geometry.